Assessment of embedded fiber Bragg gratings for structural health monitoring of composites. (May 2017) - Yeager, Mike; Todd, Michael; Gregory, William; Key, Chris
This work provides a system-level investigation into the use of embedded fiber Bragg grating optical sensors as a viable sensing architecture for the structural health monitoring of composite structures. The practical aspects of the embedding process are documented for both carbon fiber–reinforced polymer and glass fiber–reinforced polymer structures manufactured by both oven vacuum bag and vacuum-assisted resin transfer method processes. Initially, embedded specimens were subject to long-term water submersion to verify performance in an underwater environment. A larger, more complex jointed specimen was also fabricated with a fully embedded sensor network of fiber Bragg gratings and subjected to incrementally induced bearing damage. Using commercially available interrogation hardware, a damage detection structural health monitoring algorithm was developed and deployed. The results permit statistically precise detection of low levels of connection damage in the composite specimen.